2015
DOI: 10.1371/journal.pone.0139938
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Trout Gill Ionocytes in Fresh Water and Sea Water Using Laser Capture Microdissection Combined with Microarray Analysis

Abstract: Fish gills represent a complex organ composed of several cell types that perform multiple physiological functions. Among these cells, ionocytes are implicated in the maintenance of ion homeostasis. However, because the ionocyte represents only a small percent of whole gill tissue, its specific transcriptome can be overlooked among the numerous cell types included in the gill. The objective of this study is to better understand ionocyte functions by comparing the RNA expression of this cell type in freshwater a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 87 publications
2
26
0
Order By: Relevance
“…A total of 82 successfully ligated plasmids were cloned, isolated and sequenced. The success rate for unique sequences obtained from the SSH experiment was 30.5%, which is comparable to similar studies using non-model fish (8%) (Urbatzka et al, 2013); lower relative to studies using fish model organisms (45-80%) (Marchand et al, 2006;Luckenbach et al, 2008;Leguen et al, 2015); and an improvement compared with inveretebrate species such as molluscs (6-22%) (Boutet et al, 2008;Craft et al, 2010;Ciocan et al, 2011). Duplicate sequences accounted for 27% of clones and the remaining 43% of clones could not be identified based on sequence similarities.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A total of 82 successfully ligated plasmids were cloned, isolated and sequenced. The success rate for unique sequences obtained from the SSH experiment was 30.5%, which is comparable to similar studies using non-model fish (8%) (Urbatzka et al, 2013); lower relative to studies using fish model organisms (45-80%) (Marchand et al, 2006;Luckenbach et al, 2008;Leguen et al, 2015); and an improvement compared with inveretebrate species such as molluscs (6-22%) (Boutet et al, 2008;Craft et al, 2010;Ciocan et al, 2011). Duplicate sequences accounted for 27% of clones and the remaining 43% of clones could not be identified based on sequence similarities.…”
Section: Discussionsupporting
confidence: 58%
“…Laser Capture-Microdissection (LCM) allows the ability to view and dissect target cells microscopically, thereby providing a direct link between a specific histopathological lesion and the molecular profile of that lesion (Gillespie et al, 2001). LCM has previously been applied to pathological studies in aquatic organisms including fish (Vinas and Piferrer, 2008;Jorgensen et al, 2009;Kitahashi et al, 2009;Lerebours et al, 2013;Nowak et al, 2013;Leguen et al, 2015;Schaeck et al, 2016), crustaceans (Small et al, 2008), and cnidarians (Wiebring et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Both H + -ATPase (Galvez et al, 2002) and CAc ( present study) are expressed by at least a subset of PNA + ionocytes. The key element of this model, the apical Cl − /HCO 3 − exchanger, remains uncertain but recently a member of the solute carrier 26 family of anion exchangers, SLC26a6, was cloned from trout (Boyle et al, 2015) and found to be expressed in a subset of ionocytes (Leguen et al, 2015; this study did not distinguish between ionocyte types). However, the relatively low number of PNA + ionocytes that exhibited CAc immunofluorescence under control conditions (i.e.…”
Section: Discussionmentioning
confidence: 82%
“…For example, the accessory cell signature included highly restricted expression of Slc26a6, an apical membrane Cl -/HCO3 exchanger, associated with gill function but until now misattributed to expression within MRCs 25,26 . We were interested to note that the markers defining the erythrocyte population, including beta-globin, were expressed widely among all cell types.…”
Section: A Single-nuclei Survey Of Atlantic Salmon Gill Cellsmentioning
confidence: 99%